A Study of Important Atmospheric Convective Indices and Their Impacts on Aviation - Sreedevi, S.; Babu, A. Narendra; Brahmanandam, P. S.; Uma, G.; Praneetha, A.; Kumar, G. Anil; Kumar, V. Naveen; Rao, M. P. (European Journal of Applied Sciences, 2022)
Studies of the environmental impact on aircraft operations always create great interest, for both the scientific and non-scientific fraternities. It has now been fairly understood that climate changes (sea level rise, enormous increase of surface temperatures, and heat waves) have significant impacts on the aviation sector while a proper knowledge of the impacts of convective activities on the aviation sector has not yet been well known. This research presents the general mechanism of a few important atmospheric indices including, convective available potential energy (CAPE), convective inhibition (CIN), and lifted index (LI) by using radiosonde (a balloon-borne instrument). Initially, convective indices over two Indian stations (coastal and inland) are presented in terms of monthly and seasonal variations. The observed trends are discussed based on the available literature. The impacts of the atmospheric indices on the aviation industry and the feasible solutions if an airplane is caught in a severe thunderstorm are discussed.